Reconstruction of a 3D Bedrock Model in an Urban Area Using Well Stratigraphy and Geophysical Data: A Case Study of the City of Palermo - Alessandro Canzoneri; Raffaele Martorana; Mauro Agate; Maurizio Gasparo Morticelli; Patrizia Capizzi; Alessandra Carollo; Attilio Sulli (Geosciences)
A multidisciplinary approach was employed to construct a three-dimensional model of the bedrock top surface within the Palermo Plain, Sicily, Italy. This urban area is characterized by a dense and extensive built environment that largely obscures its geological features, thereby emphasizing the value of geophysical methods for enhancing subsurface understanding. In this sector, Numidian Flysch deposits constitute the geological bedrock of the plain. The morphology of the top surface of this unit was reconstructed by integrating borehole stratigraphic data with both passive and active seismic surveys. Ambient noise recordings were analyzed using the Horizontal-to-Vertical Spectral Ratio (HVSR) method to obtain spectral curves. These were then inverted into seismostratigraphic models using shear wave velocity profiles derived by Multichannel Analysis of Surface Waves (MASW) and lithostratigraphic information from borehole logs. Finally, the depth of the top of the Numidian Flysch, determined from both the borehole data and the inverted seismic models, was interpolated to generate a comprehensive 3D model of the bedrock top surface.